The role of low-level laser therapy as a complementary approach in promoting wound healing among patients with diabetic foot ulcers: A systematic review - Nurwulandari, Rosana; Sari, Yunita (Malahayati International Journal of Nursing and Health Science, 2025)
Background: A common and complicated side effect of diabetes is diabetic foot ulcers (DFUs), which frequently lead to chronic wounds that are challenging to heal. Another technique that has gained interest is low-level laser therapy (LLLT), which speeds up the healing of diabetic foot ulcers. The purpose of this systematic review is to evaluate how well LLLT aids in the healing of diabetic foot ulcers that are chronic. Purpose: To assess the effects of low-level laser therapy on the healing of diabetic foot ulcers, particularly with regard to ulcer size reduction, pain relief, and overall wound healing. Method: A comprehensive search for English-language full-text studies published between 2015 and 2024 was conducted across a number of databases, including PubMed, ScienceDirect, and Google Scholar. Randomized controlled trials that assessed the impact of LLLT on diabetic foot ulcers are required for inclusion. Measurements of wound size, ulcer healing progress, and pain reduction were used to analyze the results. Results: The analysis includes seven studies that consistently showed benefits from using LLLT. Significant decreases in ulcer size, better tissue repair, and when comparing the treated groups to the control groups, pain relief was seen. Although different laser parameters, such as wavelengths and dosages, were reported in the research, all of them shown positive outcomes in terms of speeding up wound healing and lowering pain levels related to diabetic foot ulcers. Conclusion: Low-level laser therapy is a useful supplementary technique for promoting the healing of diabetic foot ulcers. Patients with chronic diabetic foot ulcers benefit from LLLT by experiencing less pain, faster wound healing, and an overall higher quality of life. To ascertain the optimal laser parameters and assess the long-term efficacy of LLLT in the management of diabetic wounds, more extensive research is necessary.